Exercise economy in skiing and running - Losnegard, Thomas; Schäfer, Daniela; Hallén, Jostein (Frontiers in Physiology, 2014)
Substantial inter-individual variations in exercise economy exist even in highly trained endurance athletes. The variation is believed to be determined partly by intrinsic factors. Therefore, in the present study, we compared exercise economy in V2-skating, double poling and uphill running. Ten highly trained male cross-country skiers (23 ± 3 years, 180 ± 6 cm, 75 ± 8 kg, VO2peak running: 76.3 ± 5.6 mL•kg-1•min-1) participated in the study. Exercise economy and VO2peak during treadmill running, ski skating (V2 technique) and double poling were compared based on correlation analysis with subsequent criteria for interpreting the magnitude of correlation (r). There was a very large correlation in exercise economy between V2-skating and double poling (r = 0.81) and a large correlation between V2-skating and running (r = 0.53) and double poling and running (r = 0.58). There were trivial to moderate correlations between exercise economy and VO2peak (r = 0.00-0.23), cycle rate (r = 0.03-0.46), body mass (r = -0.09-0.46) and body height (r = 0.11-0.36). In conclusion, the inter-individual variation in exercise economy could only moderately be explained by differences in VO2peak, body mass and body height and therefore we suggest that other intrinsic factors contribute to the variation in exercise economy between highly trained subjects.